The Relationship Of Age, Education, Knowledge, And Occupation Of Mothers To The Implementation Of Exclusive Breastfeeding In The City Of Binjai In 2022 - Ilvira Ulpa Ismail; Joserizal Serudji; afriwardi (Science Midwifery, 2022)
According to the Indonesian Health Profile 2021, exclusive breastfeeding coverage in North Sumatra province is only 57.88% and in Binjai city only 15.74%, while the national target in Indonesia is 80%. This study aims to look at the factors associated with the implementation of exclusive breastfeeding in the city of Binjai. The design of this research is observational analytic with cross sectional approach. The population in this study were mothers who had babies aged >6-12 months in the work area of ​​the Binjai City Health Office from May to June 2022. Sampling used proportional sampling with accidental techniques on 283 respondents. Collecting data using a questionnaire, and data analyzed using univariate test, bivariate in the form of chi-square test. The research results obtained ada the relationship between the work of breastfeeding mothers with the implementation of exclusive breastfeeding p = 0.001, there is a relationship between mother's education and the implementation of exclusive breastfeeding p = 0.022, there is a relationship between knowledge and the implementation of exclusive breastfeeding p = 0.028, there is no relationship between the age of breastfeeding mothers and the implementation of exclusive breastfeeding in the city Binjai. The conclusion of this study is that there is a relationship between mother's work, mother's education and mother's knowledge of the implementation of exclusive breastfeeding, and there is no relationship between maternal age and the implementation of exclusive breastfeeding in the city of Binjai.